Keputusan Pembelian Konsumen di Matahari Citimall Sampit: Produk, Harga, dan Promosi - Seliwati, Resa (Keizai, 2022)
The research aims to find out whether product, price, and promotion influence purchasing decisions. Matahari Citimall rarely carries out promotions on social media such as discounts so people are not aware of marketing information. This study used a quantitative methodology, with a sample of 100 respondents. This survey collects product, price, promotion, and purchase decision data using a Likert scale. This study uses a multiple linear regression approach using SPSS Version 22 software. Based on the results of this study, purchasing decision behavior is not formed by price variables, but by products and promotions. Therefore, Matahari Citimall should maintain the quality of the products they sell and increase the display of promotions through Instagram and SMS media.